Relationships of Rheumatoid Factor with Thickness of Retina and Choroid in Subjects without Ocular Symptoms Using Swept-Source Optical Coherence Tomography - Li, Qingjian; Qian, Yiwen; Xu, Sennan; Zhang, Minjie; Liang, Xu; Che, Xin; Jiang, Jing; Liu, Zuguo; Zhang, Yu; Liu, Yan; Wang, Zhiliang (Journal of Immunology Research, 2021)
Purpose. Researches have confirmed that the retinal and choroidal thickness in patients with autoimmune disease-associated uveitis displays significant changes. However, the relationships between rheumatoid factor (RF) and thickness of the retina and choroid in individuals without ocular manifestations remain unclear. The aim of this study is to assess the associations of RF with retinal and choroidal thickness. Methods. The individuals enrolled in the cross-sectional research received full ocular examinations. The participants were classified as the RF (+) group (RF≥15.0 IU/ml) and the RF (−) group (RF<15.0 IU/ml) according to the serum RF titers. The thickness of the retina and choroid was measured by swept-source optical coherence tomography (SS-OCT). Results. The study covered 65 right eyes of 65 individuals that are RF-positive and 130 right eyes of 130 age- and sex-matched individuals that are RF-negative. The RF (+) group showed decreased choroidal thickness that achieved statistical significance only in the outer inferior and outer temporal sectors, as compared to the RF (−) group. There was no statistically significant difference regarding the retinal thickness between the two groups. Pearson’s correlation analysis revealed that the RF was significantly negatively related to the choroidal thickness in all areas. However, there was no significant correlation between the RF and the retinal thickness. Conclusions. Serum RF titers are closely linked with choroidal thickness before the emergence of ocular symptoms. Research into the relationships may improve our understanding of the role of serum RF in the pathogenesis of uveitis.